The Barthesian notion of myth - Kwe, Marie Abelyn C. (UP Los Baños Journal, 2013)
There is plain truth in the cliche that says, "Signs are everywhere." One way of understanding the world is looking at how everything around us-from everyday things to forms of human expression and interaction-belongs to a network of signs. This structure enables a world of meaning, where the material world which we perceive, connects to an abstract world inside our minds. Through the work of Roland Barthes, we are introduced to the notion of a sign. However, it is a structure that is artificial rather than natural and arbitrary rather than true. In addition, it is a politicized structure where meaning arbitrary as it is, is shaped by dominant ideologies. Such is the Barthesian motion of myth. It is a tool of power and oppression that preys an existing signs structures. And in as much as the world is already organized by signs, the world thus becomes rife with myths.